2021
DOI: 10.1155/2021/6616133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Effect of the Extracts of the Pods of Piliostigma thonningii (Schumach.) Milne-Redh. (Fabaceae)

Abstract: Plants have been used traditionally by people in treating and the management of diseases since time immemorial. Traditional medicines including the herbal medicines are used for primary healthcare in some domains in almost every country. Approximately 80% of the population in developing coutries depend on plants as their source of medicine for combating diseases. New and effective antimicrobial agents that have novel mechanism of actions are required. Piliostigma thonningii (Schumach.) Milne-Redh. is a species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…This plant is rich in flavonoids such as quercetin derivatives and C-methyl flavanols [ 84 , 127 ]. In addition, a kaurane diterpenoid was isolated [ 128 ]. An in-depth investigation of Piliostigma thonningii resulted in the isolation of two compounds, methyl-ent-3- β -hydroxylabd-8(17)-en-15-oate and 2 β -methoxyclovan-9 α -ol along with 14 other known compounds, e.g., flavonoids compounds (quercetin-3- O -rhamnoside) and vitamins [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…This plant is rich in flavonoids such as quercetin derivatives and C-methyl flavanols [ 84 , 127 ]. In addition, a kaurane diterpenoid was isolated [ 128 ]. An in-depth investigation of Piliostigma thonningii resulted in the isolation of two compounds, methyl-ent-3- β -hydroxylabd-8(17)-en-15-oate and 2 β -methoxyclovan-9 α -ol along with 14 other known compounds, e.g., flavonoids compounds (quercetin-3- O -rhamnoside) and vitamins [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the raw material for drugs are obtained from medicinal plants which are composed of bioactive compounds with proven efficacy because they have a vast and diverse assortment of organic compounds that can produce a definite physiological action on the human body. 2 Medicinal plants have been used from ancient times as remedies for human diseases. They contain different constituents, usually their secondary metabolites, which have various pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%